IMPACT OF PARENTAL BINGE EATING DISORDER: EXPLORING CHILDREN'S EMOTIONAL/BEHAVIORAL PROBLEMS AND THE QUALITY OF PARENT–CHILD FEEDING INTERACTIONS. Issue 5 (7th August 2018) - Cimino, Silvia; Cerniglia, Luca; Porreca, Alessio; Ballarotto, Giulia; Marzilli, Eleonora; Simonelli, Alessandra
ABSTRACT: This study examines psychopathological problems in children of parents with binge eating disorder (BED), particularly the effect of parental diagnosis on their offspring's psychopathology and the mediating power of the quality of parent–infant feeding interactions. Two hundred parents and their offspring were administered a questionnaire for the assessment of their children's psychopathology at 18 (T1) and 36 (T2) months of age. An observational measure to evaluate feeding interactions was administered at T1. Children with both parents with BED showed the highest affective, anxiety, oppositional/defiant, and autism spectrum problems, but no influence of paternal diagnosis was found on the offspring's psychopathology. Maternal BED had an influence on children's affective and autism spectrum problems, and diagnosis of BED in both parents had an effect on infants' affective problems. Paternal BED had an effect on oppositional/defiant problems through the quality of father–infant interactions, and maternal BED had an effect on the offspring's affective and anxiety problems through the mediation of mother–infant interactions. These results suggest the importance of intervention programs focusing both on parental psychopathology and on mother–child and father–child feeding interactions in families with parents with BED.